Experiences with opt-in, at-home screening for SARS-CoV-2 at a primary school in Germany: an implementation study - Wachinger, Jonas; Schirmer, Maximilian; Täuber, Nicole; McMahon-Rössle, Shannon A.; Denkinger, Claudia M. (BMJ paediatrics open, 2021)
Background Over the course of the pandemic, many countries have repeatedly closed schools and shifted schoolchildren to remote learning. However, evidence for negative mental and physiological health consequences of such measures for schoolchildren is increasing, highlighting the need for evidence-based recommendations on how to safely reopen schools. This study aims to assess implementation experiences, acceptability and feasibility of opt-in, at-home SARS-CoV-2 screening using rapid diagnostic tests (RDTs) to facilitate safe face-to-face teaching during a pandemic. - Methods We present data from a prospective study implementing an RDT-based screening programme at a primary school in southwest Germany. In addition to quantitative data collected to assess screening diagnostic yield (number of participants, tests handed out to participants, positive RDT results reported), we conducted qualitative in-depth interviews with participating pupils, parents and school stakeholders to elicit implementation experiences and screening perceptions. - Results The screening intervention was highly accepted and appreciated among participants; no screening-associated positive RDT was reported over the duration of the study. Self-testing at home before coming to school was feasible, but more positive consequences of screening participation (eg, easing of mask mandates) besides a personal feeling of safety would have been appreciated across respondent groups. Participants preferred home-based RDTs over some other measures, particularly mask mandates. Despite the RDTs being licensed as self-tests in Germany, additional training can help avoid mistakes, and ensuring intervention ownership and improving pre-implementation communication can facilitate buy-in. - Conclusions Antigen-RDT-based SARS-CoV-2 screening programmes relying on self-testing at home are a feasible and acceptable supplement to the public health toolbox to facilitate a safe return to face-to-face teaching at schools. - Trial registration number DRKS00024845.